Exploring the Challenges of English Extracurricular on Students’ Speaking Ability of 10th Grade at Diniyyah Pasia Boarding - Farhania Farhania; Absharini Kardena; Widya Syafitri; Loli Safitri (Jurnal Masyarakat Madani Indonesia, 2026)
This study aims to analyze the implementation of the English extracurricular program in relation to students' speaking ability at Diniyyah Pasia Boarding School. This research applies a qualitative approach with a case study method. Data were collected through interview the students grade 10th and a mentor, observations of extracurricular activities, as well as documentation. This study finds that the English extracurricular program runs regularly with a structured schedule, yet its effectiveness in improving students' speaking skills is hindered by limited variety in teaching methods, lack of supporting media like audiovisual tools, activities (such as public speaking and conversation) misaligned with students' interests and levels, and time constraints preventing equal speaking opportunities. While regular participation boosts confidence in some students, innovations in teaching approaches, integration of learning media, and tailored activity content are recommended for greater impact.